Sexy, Docile Bodies: The Objectification and Paternalistic Management of Plus-Size Models - Czerniawski, Amanda M. (The Contemporary Reader of Gender and Fat Studies, 2023)
This chapter examines the role of fat stigma, discipline, and sexualization in plus-size modeling. Plus-size models enter the field of fashion and are soon controlled by paternalistic management practices. They engage in an aesthetic labor process that transforms them into marketable products. Under the gaze of the cosmetic panopticon, these models become docile bodies prone to disembodiment. Ultimately, the only progress made around the conversation over beauty and body positivity is that more types of bodies are subject to objectification. This chapter examines the role of fat stigma, discipline, and sexualization in plus-size modeling. Plus-size models enter the field of fashion and are soon controlled by paternalistic management practices. The culture, via media, medicine, and state actions, legitimizes ideologies that privilege the thin body and shed an unflattering spotlight on fat. Western consumer culture places a high premium on the look and shape of bodies. Many of the women had grown up struggling with their bodies, spending years in shame, and trying to cover up their self-perceived flaws; yet, when they discovered plus-size modeling, the way they saw themselves was transformed. Models spend significant time and attention preparing their bodies for the performance of modeling. As freelance workers, models continue to modify their physical capital amid fluctuating conditions in the fashion market, as their agents guide and approve their actions.